Effect of Different Environmental and Nutritional Factors on Biosurfactant Production from Candida guilliermondii - I. M. Joaad, Ahmed; S. Hassan, Shatha (Iraqi Journal of Science, 2023)
Yeast strain S9, which produced a high amount of biosurfactant, was isolated from pickledolive and identified as a strain of Candida guilliermondii using VITTEK 2 compact system, this strain was selected out of 13bioemulsifier producing strains. The effects of some environmental and nutritional factors on biosurfactant production were evaluated, the maximum value of E24% was observed at pH 4 which was 70% and the optimal temperature for biosurfactant production was 30 °C, E24% was 75%. Among different edible and heavy oils, the sesame oil and heavy oil 150 were the best carbon sources in production of biosurfactant, E24% was82% and 78% respectively and among different organic and inorganic nitrogen sources, the yeast extract was the best organic nitrogen source for biosurfactants production, E24% was 85%, while NaNo3 was the best inorganic nitrogen source for biosurfactants production, E24% was 80% and at the 7th day the maximum production of the emulsifier, E24% was 75% in shaking incubator at 150 rpm